Antidiabetic activity of dihydropyrimidine scaffolds and structural insight by single crystal x-ray studies - Bairagi, Keshab M.; Younis, Nancy S.; Emeka, Promise M.; Sangtani, Ekta; Gonnade, Rajesh G.; Venugopala, Katharigatta N.; Alwassil, I. Osama; Khalil, Hany E.; Nayak, Susanta K. (Medicinal Chemistry, 2020)
Background: This research project is designed to identify the anti-diabetic effects of the newly synthesized compounds to conclude the perspective of consuming one or more of these new synthetic compounds for diabetes management. Introduction: A series of dihydropyrimidine (DHPM) derivative bearing electron releasing and electron-withdrawing substituent's on phenyl ring (a-j) were synthesized and screened for antihyperglycemic(anti-diabetic) activity on streptozotocin (STZ) induced diabetic rat model. The newly synthesized compounds were characterized by using FT-IR, melting point, H-1 and C-13 NMR analysis. The crystal structure and supramolecular features were analyzed through single-crystal X-ray study. Anti-diabetic activity testing of newly prepared DHPM scaffolds was mainly based on their relative substituent on the phenyl ring along with urea and thiourea. Among the synthesized DHPM scaffold, the test compound c having chlorine group on phenyl ring at the ortho position to the hydropyrimidine ring with urea and methyl acetoacetate derivative shows moderate lowering of glucose level. However, the title compounds methyl 4-(4-hydroxy-3-methoxyphenyl)-6-methyl-2-thioxo-1,2,3,4-tetrahydropyrimi dine-5-carboxylate(g) and ethyl 4-(3-ethoxy-4-hydroxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydroprimidine- 5-carboxylate(h) having methoxy and ethoxy substituents on phenyl ring show significant hypoglycemic activity compared to the remaining compounds from the Scheme 1. Methods: The experimental rat models for the study were divided into 13 groups (n = 10); group 1 animals were treated with 0.5% CMC (0.5mL) (vehicle); group 2 were considered the streptozotocin (STZ)/nicotinamide diabetic control group (DC) and untreated, group 3 diabetic animals were administered with gliclazide 50 mg/kg and act as a reference drug group. The remaining groups of the diabetic animals were administered with the newly synthesized dihydropyrimidine compounds in a single dose of 50 mg/kg orally using the oral gavage, daily for 7 days continuously. The blood glucose level was measured before and 72 hrs after nicotinamide-STZ injection, for confirmation of hyperglycemia and type 2 diabetes development. Results: Blood glucose levels were significantly (p<0.05) reduced after treatment with these derivatives. The mean percentage reduction for gliclazide was 50%, while that of synthesized compounds were approximately 36%. Conclusion: Our result suggests that the synthesized new DEEM derivative containing alkoxy group on the phenyl ring shows a significant lowering of glucose level compared to other derivatives.
Keywords: anti-Diabetic; blood glucose levels; dihydropyrimidine; hypoglycemic activity; Streptozotocin; type 2 diabetes mellitus